2008
DOI: 10.1111/j.1365-2966.2008.13291.x
|View full text |Cite
|
Sign up to set email alerts
|

Binary star origin of high field magnetic white dwarfs

Abstract: White dwarfs with surface magnetic fields in excess of 1 MG are found as isolated single stars and relatively more often in magnetic cataclysmic variables (CVs). Some 1253 white dwarfs with a detached low-mass main-sequence companion are identified in the Sloan Digital Sky Survey (SDSS) but none of these is observed to show evidence for Zeeman splitting of hydrogen lines associated with a magnetic field in excess of 1 MG. If such high magnetic fields on white dwarfs result from the isolated evolution of a sing… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
264
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 235 publications
(277 citation statements)
references
References 33 publications
12
264
1
Order By: Relevance
“…Alternatively, Tout et al (2008) suggested that high magnetic field white dwarfs may form via strong binary interactions between a main sequence and red giant (and hence white-dwarf progenitor) in a common envelope phase. In this scenario as the orbital period of the 2 components decreases, differential rotation within the convective common envelope generates the magnetic field via dynamo action; one might speculate that a comparable process also occurs in high mass analogues, such as the pre-SN LBV/common envelope phase we propose here (Sect.…”
Section: Implications For Magnetar Formationmentioning
confidence: 99%
“…Alternatively, Tout et al (2008) suggested that high magnetic field white dwarfs may form via strong binary interactions between a main sequence and red giant (and hence white-dwarf progenitor) in a common envelope phase. In this scenario as the orbital period of the 2 components decreases, differential rotation within the convective common envelope generates the magnetic field via dynamo action; one might speculate that a comparable process also occurs in high mass analogues, such as the pre-SN LBV/common envelope phase we propose here (Sect.…”
Section: Implications For Magnetar Formationmentioning
confidence: 99%
“…An additional, later, source or sink of angular momentum for WDs in close binaries could be torques induced during common-envelope phases, Roche-lobe overflow accretion from a companion, or merger with another WD or stellar core (e.g. Tout et al 2008).…”
Section: Wd Rotationmentioning
confidence: 99%
“…It has been proposed that they may be the fossil remmnants of magnetism inherited from an earlier stage of evolution, for example from the main sequence (Landstreet 1992). Alternatively, the fields of white dwarfs may have a more specific origin, such as being produced during the mergers of close binary systems Tout et al 2008;Wickramasinghe et al 2014). …”
Section: Introductionmentioning
confidence: 99%